Environmental economic valuation: the problem of social cost - Raffo Lecca, Eduardo (2016)
Environmental economic valuation seeks a monetary measurement of the gain or loss of welfare or utility that an individual or a particular group experience, because of improved or damaged environmental asset accessible to such person or group. The study concludes that the environmental components perform functions that maintain the conditions of ecosystems and the atmosphere, so that the State establishes mechanisms to enhance environmental services, seeking to ensure the conservation of ecosystems, biodiversity and other resources natural.